La classe inversée comme approche pédagogique en enseignement supérieur : état des connaissances scientifiques et recommandations - Marco Guilbault; Anabelle Viau-Guay (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Many spheres of society put pressure on higher education so that the needs of the learner are better taken into account. The flipped classroom could have positive impacts on both learning and learner satisfaction. This article presents an overview of the research on flipped classroom in higher education. For this review we have selected articles related to the post-secondary level in a variety of disciplines from the years 2000 to 2015. The results show the positive impacts and the limits of such an approach with an emphasis on the point of view of teachers and students. Recommendations have been formulated based on the survey of literature. The article provides a theoretical base to fully understand the flipped classroom in action and a tool to ease its mobilization in any discipline.